Halal Tourism In West Nusa Tenggara: A Legal And Economic Perspective - Dwi Martini; I Gusti Ayu Oka Netrawati; Sri Maryanti; Febrian Humaidi Sukmana (Fakultas Hukum Universitas Mataram, 2020)
This research aims to find out the implementation forms of halal tourism through establishment of local law as well as to find out it impact toward economic development in Nusa Tenggara Barat. This article examines several questions namely what is the implementation forms of the local laws regarding halal tourism and what are the impact of the local law toward economic development in West Nusa Tenggara. The problem formulations are examined using qualitative research method which applying document studies and in-depth interviews with relevant informant. Research result indicates that the implementation of the Perda is not fully strict due to business consideration and calculation. Halal tourism brought positive economic effect especially in terms of job variety and income improvement. It can be concluded that halal tourism concept in NTB is not fully implement Syariah compliance and there is an increase trend of tourists visit to NTB after halal tourism was introduced.